A REVIEW OF GREEN ACCOUNTING IN EMERGING ECONOMIES (American Journal of Business Management, Economics and Banking, 2025)
This study conducts a comprehensive meta-synthesis of review-based research on green accounting, spanning from 2020 to 2024. Green accounting, also known as Environmental accounting, has evolved as a critical tool for integrating sustainability into corporate financial practices. The analysis was performed using a CSV file, Microsoft Excel 2021, and RIS.The findings highlight a significant increase in review-based studies since 2020, coinciding with the growing global awareness and importance of sustainability. This study contributes to the field by consolidating fragmented research on green accounting, offering a framework for future academic exploration. Practically, it informs policymakers and business leaders on the importance of unified reporting standards across regions; integrating environmental considerations into financial decision-making; promoting transparency, accountability, and sustainability accounting; and disclosure across industries and regions.